Strategic Development of International Corporate Social Responsibility in Agribusiness - Soloviova, Olha; Krasnyak, Olena; Cherkaska, Valeriy; Revkova, Anna (Dr. Viktor Koval, 2022)
Introduction. The identification of the interdependent development of society and business contributed to the introduction of corporate social responsibility in entrepreneurship as a guarantee of obtaining from its activity not only an economic effect but also the stimulation of social and environmental development. After all, the development of society requires constant changes in the consumption of various types of goods and services under the condition of a safe level of ecology and agriculture as the basis of food security in society, which necessitates the stimulation of productive activities of corporate social responsibility in agrarian business and its serving industries. Aim and tasks. The aim of the study is an analysis of the strategic development of international corporate social responsibility in agribusiness. The main tasks are: to investigate the modern strategic directions of the development of corporate social responsibility, focusing on agrarian businesses, to identify problems and find resources to overcome them. Results. Strategies for the development of corporate social responsibility in business are generally formed in relation to the goals and directions of the development of business activity and aim, as a final result, to increase the level of development of business activity, society, and preservation and protection of the environment. Social, ecological, economic, intra-economic, and external strategic directions of CSR influence have been identified, with implementation carried out directly by enterprise employees or with the assistance of interested participants, or "stakeholders." An analysis of CSR business strategies was carried out with the aim of forming the optimal option for obtaining mutual benefits for all interested parties. It was determined that the relevant strategies do not have permanence and need improvement, correction, and adaptation in accordance with evolutionary changes in the development of society. Conclusions. The process of implementing CSR in business has a long-term nature and requires determining the optimal relationship between the chosen areas of social responsibility development in combination with the economic activity of business structures. The main directions of CSR development in agribusiness are assistance and promotion of the development and motivation of labor personnel; introduction of waste-free economic production; maintenance of relationships with clients; brand distribution; and environmental protection. The international direction of CSR is oriented in the direction of "green activity," affecting the reduction of the level of poverty and inequality.